2013
DOI: 10.1155/2013/348250
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Opportunistic Pathogenic Bacteria in Drinking Water Samples of Different Rural Health Centers and Their Clinical Impacts on Humans

Abstract: International drinking water quality monitoring programs have been established in order to prevent or to reduce the risk of contracting water-related infections. A survey was performed on groundwater-derived drinking water from 13 different hospitals in the Mahabubnagar District. A total of 55 bacterial strains were isolated which belonged to both gram-positive and gram-negative bacteria. All the taxa were identified based on the 16S rRNA gene sequence analysis based on which they are phylogenetically close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
2
14
0
1
Order By: Relevance
“…Pindi et al17 reported similar results that phylogenetic analysis based on 16S rRNA gene sequences indicated that the 21 Acinetobacter strains belonged to 4 groups, 9 Bacillus strains belonged to 7 groups, 8 Pseudomonas strains belonged to 3 groups, 7 Aeromonas strains belonged to 5 groups, and 2 Methylobacterium strains formed two distinct groups17,18 which indicated the originality and authenticity of our study data.…”
Section: Discussionsupporting
confidence: 77%
“…Pindi et al17 reported similar results that phylogenetic analysis based on 16S rRNA gene sequences indicated that the 21 Acinetobacter strains belonged to 4 groups, 9 Bacillus strains belonged to 7 groups, 8 Pseudomonas strains belonged to 3 groups, 7 Aeromonas strains belonged to 5 groups, and 2 Methylobacterium strains formed two distinct groups17,18 which indicated the originality and authenticity of our study data.…”
Section: Discussionsupporting
confidence: 77%
“…Several of the isolated bacteria, such as K. pneumoniae, Enterobacter spp., Proteus spp., Providencia spp. and Citrobacter spp., are known to cause diseases in avian species, as well as in mammals and humans (Reslinski et al 2005;Pindi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The intake of water polluted with faeces or human waste and the acquisition via food seem to be the sources of transmission of resistant bacteria of human and veterinary origin to wild birds (Reed et al 2003;Pindi et al 2013;Pinto et al 2015). Birds not only acquire pathogens from the environment, but also return them via excretion, potentially facilitating the dissemination of pathogenic organisms to both humans and other animals, especially through water (Benskin et al 2009;Wellington et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate access to clean water, inappropriate water treatment and bad sanitation systems is one of the most pervasive issues distressing people throughout the globe, causing waterborne infectious diseases, cause approximately 10 million deaths per year [3,20,21]. Human health is prone to microbial risks caused by enteric viruses and bacteria [22].…”
Section: Discussionmentioning
confidence: 99%